Factors Affecting Customer’s Behavior and Intention on Purchase Intention through Brand Retail’s Social Media - Setiawan, Yusup; Hamdi, Edi (Interdisciplinary Social Studies, 2022)
Background: The increasing use of social media to sell products and the huge number of social media’s users makes the study consumer-brand engagement behavior within social media, Facebook in particular, necessary. Aim: This study aims to examine 5 antecedents of attitude on consumer intentions to engage with retail brand through social effecting the likelihood to make purchases as well as an antecedent moderation of attitude on the intention to make purchases. Method: The study is conducted on office workers using quantitative survey methods to 195 respondants. The analysis is conducted by using the Structural Equation Model (SEM). Findings: The findings reveal that while the consumer attitudes to engage with retail brands through Facebook are driven by enjoyment, peer communication, and credibility, the attitudes have strong influence to the intentions to engage with retail brands through Facebook and subsequently are strongly connected with the intentions to purchase through a retail brand’s Facebook page. These findings support prior studies. The findings are that consumers’ attitudes have positive effects on consumer intentions, and that the confirmation of expectation moderates the attitude on consumer intentions to make purchase through a retail brand’s Facebook page. The managerial contribution of this study helps retailers to understand how to attract consumers to engage with retail brands through Facebook.